Penerapan Model Problem Based Learning untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas VIIIC MTsN 3 Siak - Fahratul Aini; Syarifah Nur Siregar; Elfis Suanto (Aksioma, 2026)
This research is motivated by the low mathematics learning outcomes of class VIIIC students of MTsN 3 Siak in the 2024/2025 academic year. The purpose of this study is to improve learning and improve mathematics learning outcomes by implementing the Problem Based Learning learning model. This research was conducted in two cycles and the subjects of the research were class VIIIC students of MTsN 3 Siak in the even semester of the 2024/2025 academic year totaling 27 students. The research focuses on student activities and student learning outcomes. Observation sheets and learning outcome tests were used as data collection methods. The results of this study indicate that the learning process has increased after the implementation of the PBL model. The percentage of students who achieved KKTP from the basic score to the summative test I and from the summative test I to the summative test II each increased, namely from 33.33% to 51.85% then 70.37%. From the data analysis, it was concluded that the application of the Problem Based Learning model can improve the learning process and improve the mathematics learning outcomes of students who achieved KKTP in class VIIIC MTsN 3 Siak